3-E feasibility analysis on photovoltaic/thermal application for residential buildings: a case study of Sub-Saharan Africa. Issue 4 (21st December 2022) - Adun, Humphrey; Ishaku, Hamagham Peter; Ayomide Titus, Ogungbemi; Shefik, Ali
ABSTRACT: This study was driven by the need to comprehend and give long-term answers to Nigeria's ongoing energy crises and energy famine, despite the country's tremendous endowment of renewable energy. The first step toward proffering such solutions is to present the potential benefits of solar-driven technology for residential applications. This study simulates the performance of a photovoltaic/thermal system for electricity and hot water production for a typical four-person residential settlement in different regions in Nigeria. This study computes the economic feasibility, as well as the environmental implications of the proposed PVT system on the considered geopolitical zones in Nigeria. The performance of the system were assessed on a technical, economic and environmental basis. Final system yield, performance ratio, electrical efficiency, and solar fraction were used for technical assessments, and cost savings was used for economic analysis. The relevant finding revealed that the maximum final yield (in this study) of 159kWh/kWp is retrieved in Maiduguri, while the least final yield of 75.8kWh/kWp is retrieved in Port Harcourt. The northeast (Maiduguri) showed the best annual final yield of 1735kWh/kWp. Onitsha and Port Harcourt showed a maximum performance ratio of 76.3%, and 76.2% respectively. The value of LCOE obtained in this study is in the range of 0.2518$/kWh-0.3838$/kWh, with an average of 0.3056$/kWh